Clinical Analysis of Macular Edema with New Software for SD-OCT Imaging. Issue 6 (November 2013) - Azzolini, Claudio; Sansoni, Giovanna; Donati, Simone; Parodi, Maurizio Battaglia; Oum, Muna Al; Vinciguerra, Riccardo; Tartaglia, Valerio; Semeraro, Francesco; Virgili, Gianni
Purpose: To evaluate the clinical efficacy of user-friendly software for the measurement of intraretinal hyporeflective spaces expression of macular edema . Methods: Fifteen consecutive patients with diabetic retinopathy with clinically significant macular edema were examined using conventional spectral domain optical coherence tomography (OCT). A new composite software application, OCT–measurement analysis tool (OCT-MAT), was developed to automatically process and analyze OCT B-scans by means of image acquisition, filtering, and elaboration, together with hyporeflective area recognition and measurement in μm 2 . The same macular areas were measured manually, and then compared to the measurements obtained by the automated OCT-MAT software. A statistical t test analysis was applied (statistical significance level at p<0.05). The repeatability and reproducibility coefficient for the automated software was computed using the Wilcoxon matched pair test (5% significance level) . Results: In all patients, the software effectively measured the number and extension of intraretinal hyporeflective spaces in μm 2 . The comparison between mean manual measurements and OCT-MAT measurements (0.478 ± 0.300 × 10 6 μm 2 vs 0.471 ± 0.321 × 10 6 μm 2 ) showed correct correspondence (p>0.05). Moreover, the OCT-MAT software showed good repeatability and reproducibility (coefficient below 3%) . Conclusions: OCT-MAT allows the precise measurement of macular edema in terms of the number of empty spaces and their size in all patients. Its daily clinical application might give precise information regarding the evolution of macular edema and the efficacy of therapy .